2014
DOI: 10.3402/tellusa.v66.22377
|View full text |Cite
|
Sign up to set email alerts
|

Climatology of the Iberia coastal low-level wind jet: weather research forecasting model high-resolution results

Abstract: A B S T R A C T Coastal low-level jets (CLLJ) are a low-tropospheric wind feature driven by the pressure gradient produced by a sharp contrast between high temperatures over land and lower temperatures over the sea. This contrast between the cold ocean and the warm land in the summer is intensified by the impact of the coastal parallel winds on the ocean generating upwelling currents, sharpening the temperature gradient close to the coast and giving rise to strong baroclinic structures at the coast. During sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 62 publications
(92 citation statements)
references
References 47 publications
6
84
2
Order By: Relevance
“…The heat low generates low-level wind jets along the coastal areas of the IP (Soares et al, 2014), which underlie the nearly circular shape of the trajectory densities. In contrast to winter, the association with teleconnection patterns, such as the NAO and EA, is less clear in summer, when the North Atlantic large-scale atmospheric circulation is generally much weaker ( Barnston and Livezey, 1987).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The heat low generates low-level wind jets along the coastal areas of the IP (Soares et al, 2014), which underlie the nearly circular shape of the trajectory densities. In contrast to winter, the association with teleconnection patterns, such as the NAO and EA, is less clear in summer, when the North Atlantic large-scale atmospheric circulation is generally much weaker ( Barnston and Livezey, 1987).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Upwelling alters the seasurface temperature (SST) pattern along the coast by lowering the ocean temperature, and consequently, intensifies the landÁsea temperature, and hence pressure gradient, strengthening the wind speed and CLLJ occurrences through positive feedback along the coast (Rijo et al, 2014;Soares et al, 2014). This decrease of SST along the coast also lowers the ocean surface evaporation, which combined with the strong coast-parallel winds, limits the onshore moisture advection and contributes to the aridity and dryness of some of the mid-latitude western coastal regions (Warner, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…To further investigate the causes of these wind features, three events representative of each location and strength categories were selected. It was demonstrated that, for the three events, a LLCJ was present consistently with studies conducted by other authors for the region [ Ranjha et al ., ; Soares et al , ], establishing the background conditions in which MABL response can occur. In the three events studied, a distinct low atmosphere temperature inversion capping the MABL was found south of 42°N.…”
Section: Discussionmentioning
confidence: 99%